Avoidant attachment and own and perceived partner's conflict resolution in relationship satisfaction. (December 2020) - Bretaña, Ione; Alonso-Arbiol, Itziar; Molero, Fernando; Pardo, Juan
The aim of this study was to analyze the effect of conflict resolution strategies in the links between the avoidant attachment dimension and relationship satisfaction. The sample comprised 274 participants (ranging from 18 to 73 years old, 58% women). A predictive model of relationship satisfaction was tested, taking into account avoidant attachment and both own and perceived partner's conflict resolution strategies. Structural equation modeling was used. Fit indexes indicated that the suggested overall relationship model was confirmed. Own withdrawal conflict resolution was associated positively with individuals' perception of partner demand. Specifically, there was an indirect effect between own withdrawal and relationship satisfaction mediated by demand strategy perceived in the partner. Own withdrawal was negatively associated with perceived partner's problem solving, and perceived partner's positive conflict resolution strategy was positively associated with relationship satisfaction. Practical implications for professionals working with couples are discussed.